THE DIFFERENCES OF PREGNANT WOMEN KNOWLEDGE LEVEL IN THE OWNERSHIP OF MCH HANDBOOK - Anisah Sri Utami; Djohar Nuswantoro; Ivon Diah Wittiarika (Indonesian Midwifery and Health Sciences Journal, 2020)
AbstractBackground: The MCH (Maternal Child Health) Handbook is a mandatory handbook for mother and children that has function as information especially for pregnant women until childbirth and also newborn to toddlers. One of the utilization of MCH Handbook is by an active reading role is considered to be able to  achieve the goal so that mothers can carry out health care independently so that pregnant women can detect complications as early as possible. Method : The research method is analytic Observational with cross-sectional design. The total sample is 114 pregnant women, using purposive sampling technique. The independent variable is the ownership of MCH Handbook which is categorized in 3 groups of reading activities and the dependent variable is the level of knowledge. Data analysis using Kruskal Wallis test. Result : The result showed that pregnant women who read entire contents of the MCH Handbook had a good level of knowledge is 47 respondents and none had sufficient or insufficient knowledge, while pregnant women who read some of the contents of the MCH Handbook had a good level of knowledge is 55 people and 2 others had enough knowledge.For the group of pregnant women who did not read the contents of MCH Handbook, there were 10 people and all of them had a good level of knowledge. The result of Kruskal Wallis test is p values = 0,365 ( p>0,05). Conclusion : There is no different of the knowledge level on 3 reading group.